Review of the Generation of Fractures and Change of Permeability due to Water-Shale Interaction in Shales. (13th June 2022) - Liu, Kerui; Wang, Dangliang; Sheng, James J.; Li, Jianfeng
Abstract : In shale development, water-based liquids are injected into the formations. In this process, water can interact with shales, especially with clay content. The interaction can lead to some phenomena, including clay swelling, reduction of mechanical properties of shales and fractures, generation and propagation of fractures, particle detachment, and permeability change. All the phenomena can impact productivity during the development, thereby impacting our investment and return on investment (ROI). So far, many researchers have put their time and efforts into this topic, and many articles have been published. However, some discrepancies still exist in shale reservoirs regarding the role of the interaction between water and shale, especially the impact of clay swelling. Some believe that clay swelling causes formation damage, mainly impairing shale permeability. Others state that fractures can be induced because of clay swelling, leading to the enhancement of shale permeability. So far, few articles have reviewed the various views on this interaction. Additionally, the relationship between each phenomenon is not discussed. In this paper, we try to draw a clear picture of water-shale interaction by reviewing the published studies, mainly focusing on experimental methodology and experimental results. Based on the review, we summarized the influencing factors as well as the mechanisms about the formation of fractures and change of permeability due to water-shale interaction. In water-shale interaction, the induced fractures are generated by the combined effects from clay swelling, reduction of mechanical properties of shales and fractures, and stress anisotropy. Shale permeability can be enhanced if the generated fractures can form an effective flow channel. However, if the generated fractures cannot serve as an effective flow channel, shale permeability will be impaired by clay swelling, water blocking, stress-sensitive, etc.